The nutritional returns to parental education - Alderman, Harold; Headey, Derek D. (International Food Policy Research Institute, 2014)
Though parental education is widely perceived to be an important determinant of child nutrition outcomes, there remain significant uncertainties about whether maternal or paternal education matters most, whether there are increasing or decreasing returns to parental education, and whether these returns are robust given that recent gains in enrollment have not always translated into commensurate gains in learning outcomes. In this paper we investigate these questions through a statistical analysis of child growth data for approximately 99,000 children in 19 countries with some of the highest burdens of undernutrition. Pooling across countries, we find that maternal education yields larger returns than paternal education, although for both sexes positive returns generally only appear with secondary education.